Peran Sosial Finance Baitul Maal Wat Tamwil (BMT) dalam Menumbuhkan Keuangan Inklusif Studi pada BMT di Tulungagung dan Blitar - Susilowati, Lantip (Institut Agama Islam Negeri Madura, 2020)
Baitul Maal wat Tamwil has two directions, namely managing business and social affairs. The basic problem for BMT is that the management of social funds in BMT has not been maximized. This is indicated by the distribution of charity social funds. Based on these problems, this paper intends to explore how the implementation and role of BMT social finance in growing financial inclusion?. The method used is a qualitative type and descriptive approach. The results of this paper are first, the implementation of social finance are source of fund’s social finance management and distribution. Source of fund’s social finance are in the form of zakat, infaq, social funds, and distribution of social finance are social assistance, scholarship and qardul hasan financing. Second, the role of Baitul Maal wat Tamwil Pahlawan Tulungagung's social finance role in fostering financial inclusion, among others in the form of Qardh al-Hasan financing and other direct assistance. Direct assistance has no impact on savings opportunities. The role of social finance in growing financial inclusion in the BMT Podo Joyo Blitar includes, among others, the financing of Qardh al-Hasan and assistance for orphans in the form of savings accounts as well as from assistance for widows.